Adonis as a Tomb Effigy in Shakespeare’s Venus and Adonis - Láncos, Eszter (Booklets of Sárospatak, 2025)
The focus of this paper is on how the protagonists of Shakespeare’s epyllion, Venus and Adonis, relate to the themes of love, death, heroism, and memory. The analysis begins with a rarely quoted passage in which Venus rebukes Adonis for being like a "painted idol" and a "senseless stone." There is a sharp contrast between the views of the two characters: Venus prioritizes love over valor and believes that the best way to be remembered is through having offsprings, while Adonis seeks military glory and fame. This conflict is mediated through symbolic images that reflect not only on the world of mythology but also on the changing religious and cultural context of the Elizabethan era, particularly the new ways of commemorating the dead. The paper explores how Adonis's desire for heroism and Venus's words of rebuke reveal a potential approach to commemoration.